Electronic medical record use and associated factors among healthcare professionals at public health facilities in Dire Dawa, eastern Ethiopia: A mixed-method study - Tolera, Abebe; Oljira, Lamessa; Dingeta, Tariku; Abera, Admas; Roba, Hirbo Shore (Frontiers in Digital Health, 2022)
Abstract Background: Despite the significant benefits of digital health technologies (IT), the adoption of electronic medical records (EMR) in a health care setting is lagging behind in developing countries. EMRs have long been considered as essential elements in improving healthcare quality.. However, utilization of EMR among healthcare providers still remains low particularly in developing countries. Objective: This study aimed at exploring EMR use and its determinants among health care providers at public health facilities in Dire Dawa, eastern Ethiopia. Methods: Quantitative cross-sectional study was conducted among 402 health professionals working at public health facilities supplemented with an exploratory qualitative study in Dire Dawa, Ethiopia. Descriptive summary statistics and binary and multivariable logistic regression analysis were used to explore determinant factors of EMR use while qualitative data were thematically analyzed. Results: Overall, about a quarter (26.6%) of health professionals were using electronic medical records. Work experience of 6 years or less (AOR=2.23; 95% CI: [1.15-4.31]), discussion on EMR (AOR=14.47; 95% CI: [5.58-37.57]), presence of EMR manual (AOR=3.10 95%CI: [1.28-7.38]), and positive attitude towards EMR system (AOR=11.15; 95%CI: [4.90-25.36]) and service quality (AOR=8.02; 95% CI: [4.09-15.72]) were independent determinants of EMR use. Poor collaboration among stakeholders and dependence on NGOs’ software programs were the main challenges cited by key informants. Conclusion: This study’s findings indicate that EMR use by health professionals in the study area is very low. Several organizational, technical, and behavioral factors were identified for this low utilization. Therefore, there is a need to leverage through continuous technical support and commitment to enhance EMR use which has the potential to improve health service performance. Developing local applicable EMR software should be considered.